An experimental and mechanical approach to predicting erosion of powdery soils - ENYEGUE, Timothée Thierry; Mbiakouo-Djomo , Eric Flavien; Ngwem Bayiha , Blaise; Kemogne, Fabien; Fokwa, Didier (European Journal of Applied Sciences, 2022)
The study of erosion is very complex because it is influenced by several spatio-temporal parameters. We propose in this article a simplistic approach, based on the laws of mechanics. A mechanical modeling is made from the dynamics of the fluid-particle interaction, making it possible to highlight the process of particle transport by a fluid flow. The data used are obtained from studies carried out on a rain simulator. The resolution of the equations is done analytically and numerically. This new approach is particularly interested in the contribution of water flow to the erosion phenomenon. It provides a good understanding of the evolution of runoff erosion, by transport of particles initially torn off by the splash phenomenon. The results obtained show that the flow velocity decreases when the particle masses increase, which confirms the assertion that low velocities cause large soil losses, due to the intensification of friction in the fluid interface. particle, unlike high-speed flows which, due to slips at the interface, carry away a tiny quantity of particles, not having a considerable impact on the kinetics of said flow.